Konstruksi Sosial Pelaku Usaha Mengenai Platrfrom Instaqris Sebagai Layanan Pendaftaran dan Pengelola QRIS - Herniah Herniah; benget Hutagaol (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2026)
The current entrepreneurial reality is largely shaped by digitalization. Business actors collectively construct an understanding that transactions do not have to be carried out in cash but also non-cash. One of the digital-based payments that is currently in demand is QRIS. To obtain a QR to be able to make transactions, business actors must register on the application. One application that can be used is InstaQRIS. The InstaQris application is the official platform and service for QRIS (Quick Response Code Indonesian Standard) registration supervised by Bank Indonesia. This service allows MSMEs, shops, and individual businesses to accept digital payments from all e-wallets and m-banking using only one QR code. This study aims to determine the social construction of business actors regarding the InstaQris application in retail kiosk business actors in Makassar. This study uses a descriptive qualitative approach with data collection methods through in-depth interviews and direct observation of retail kiosk owners who have used the InstaQris application. Based on the results of the study, several social constructions of InstaQris were found, including: 1). InstaQris is interpreted as an application that innovates in carrying out Qris registration, where the registration process is very easy and instant 2). InstaQris is interpreted as an application that facilitates transaction access, meaning they can reach a wider customer base and create a more modern impression. 3). InstaQris is interpreted as simplifying the transaction process by reducing the risk of incorrect change calculation, minimizing cash loss at businesses, and reducing the circulation of counterf